The Muslim Mind on Trial: Divine Revelation vs. Secular Rationalism by Abdessalam Yassine; tr. Muhtar Holland (Iowa City: Justice and Spirituality Publishing, 2003. 98 pages.) (American Journal of Islam and Society, 2004)
Abdessalam Yassine, a Moroccan Qur’anic scholar, passionately arguesthat Muslims need to return to the Qur’anic revelation and the propheticmethod of Prophet Muhammad (pbuh) in order to resurrect the Muslimmind and worldview, which are currently subjugated to secular westernthought. According to Yassine, the book’s purpose “is the establishmentand reminding of the Prophetic Method” (p. 25). This argument is madein the format of an introduction and 37 subject variants (ranging in lengthfrom a few paragraphs to seven pages).Yassine juxtaposes the Muslim mind with that of the secular materialisticwestern mind, where the latter is shown to be deficient while theformer, based on and nourished by revelation and the Sunnah, is consideredto be truly emancipatory. He states: “When discussing the choicebetween two minds and two mentalities we have only two options: Eitherthe sovereignty of the Revelation, pure and simple … Or the sovereignty of the arena, which occupied the other mind with its materialism, racialismand vagueness of its goals” (p. 9).Throughout the book, Yassine provides some insights into Islamicspiritual practice and critiques mainstream western thought. Interestingly,his essay “Ritual Purity” eloquently points out the importance of situatingthe body in Islamic spirituality and how its purification is interconnectedwith inner spiritual growth. In addition, he does not romanticizethe current Muslim ummah and shift all blame to the West; rather, he critiquesthe ummah for being coopted by western materialism.However, I had numerous problems with this book, beginning with itspremise. In an age of pluralistic societies, it is very hard to digest a discussionwhere one does not acknowledge that a pure “western mind” or a“Muslim mind” does not exist, because this assumption fails to acknowledgethe difference and diversity among interpretations of text and ideas.Yassine employs the dominant discourses in both western and Islamicthought in order to forward his argument, which, in turn, leads to essentialism.Knowledge production is dynamic, and constructing such a binaryframework perpetuates the idea that knowledge is static and fixed to a certaincontext, which only bolsters stereotypes ...